188k views
5 votes
Rewrite the expression in the form k times x^n

Rewrite the expression in the form k times x^n-example-1

1 Answer

4 votes


\mathbf{Task.} ~ \mathrm{Rewrite~the~expression~in~the~form~} k \cdot x^(n).


First~way\colon


\left(16\sqrt{x^(3)} \right)^{\tfrac{1}{4} }= \left(2^(4)\cdot x^{\tfrac{3}{2} } \right)^\bigg{(1)/(4) } = 2^{4 \cdot \tfrac{1}{4} } \cdot x^{\tfrac{3}{2} \cdot \tfrac{1}{4} } = 2 \cdot x^{\tfrac{3}{8} }


Second~way\colon


\left(16\sqrt{x^(3)} \right)^{\tfrac{1}{4} }= \sqrt[4]{16 \cdot \sqrt{x^(3)}} = \sqrt[4]{2^(4)} \cdot \sqrt[4]{\sqrt{x^(3)}} = 2 \cdot \sqrt[8]{x^(3)} = 2 \cdot x^{\tfrac{3}{8} }


Answer\colon~2 \cdot x^{\tfrac{3}{8} }. ~ \blacktriangle

User Kevin Wang
by
5.6k points